Effectiveness and compatibility of fabricated hydraulic lime prepared with ultrafine pozzolanic materials in consolidating soil-matrix. (16th May 2023) - Zhu, Huimei; Wu, Xingzi; Chen, Jiani; Li, Hui
Highlights: Using water as solvent was beneficial to the consolidation effect of hydraulic lime. Superfine pozzolan supplied deep penetration and slight migration for FHL in matrix. Filling and cementation of FHL formed a spatial network in consolidated soil-matrix. FHL was superior in improving mechanical properties and compatibility of soil-matrix. Abstract: In this experiment, fabricated hydraulic lime (FHL) was synthesized by blended hydrated lime and superfine pozzolanic components, and the solvent for preparing lime-suspension was optimized through a static bleeding test. A systematic comparison was conducted between a commercial natural hydraulic lime (NHL) and synthesized FHL in consolidating soil-matrix. Their effects were evaluated in terms of effectiveness (penetration depth and surface hardness) and compatibility (color difference and vapor transmission). Both consolidants were proved to be compatible, while FHL-suspension outperformed NHL in effectiveness, due to the filling effect and cementation with the original loose soil particles supplied by superfine pozzolanic components, and their quicker hydration products helped the formation of a spatial network in consolidated matrixes. In addition to the known widely available raw materials supply, this experiment confirmed the properties advantages of FHL, which supplied a potentially suitable material for the anti-weathering purpose of earthen relics.